Creating optimized machine working patterns on agricultural fields - Spekken, Mark (2015)
In the current agricultural context, agricultural machine unproductivity on fields and their impacts on soil along pathways are unavoidable. These machines have direct and indirect costs associated to their work in field, with non-productive time spent in manoeuvres when these are reaching field borders; likewise, there is a double application of product when machines are covering headlands while adding farm inputs. Both issues aggravate under irregular field geometry. Moreover, unproductive time can also appear in operations of loading/offloading the machine\'s reservoir with inputs/harvested-goods, which can increase with an improper use of the reservoir due to the inadequate machine path length. On the other hand, irregular steep surfaces present a problem for establishment of row crops and machine paths towards erosion. Though contouring (i.e., performing field operations perpendicular to slope direction) is a common practice to reduce runoff and increase water infiltration, still elevation contours are never parallel, while machine operations always are. Many of these issues were target for optimization in computer path planning for agricultural machines, where unproductivity was overall minimized and attempts of soil loss reduction by more proper path establishment also yielded results. This thesis gathered these issues in a combined path planning approach making possible to address soil loss and unproductive costs to their proper location. A number of methods was proposed and modified: creating and replicating steerable machine track; finding more optimal references for path coverage on irregular surfaces (curved or straight); quantifying the impacts of soil loss for a given path pattern; identifying spatially the water flow and concentration; defining geometrically different manoeuvre types and calculate its time, space and energy demands; obtain the overlapped area of input application; and quantifying the machine replenishment cost in relation to underuse of its reservoir for following tracks of inadequate length. An algorithm-application was achieved, which is capable of simulating a large number of path coverage scenarios and to display optimized ones based on a user defined criteria. Sugarcane crop, grown in Brazilian conditions, was the main object of study in this thesis because of its high in-field mechanization costs (along with unproductive operational costs), high susceptibility of soil erosion in its planting phase, and for occupying an area of predominant rolling surface. Case studies were subject to this algorithm that provided suitable outputs with minimized impacts. The outputs of the algorithm were comprehensive and showed potential for the methods to be used by agricultural decision makers.